New Report of Cyanobacteria and Cyanotoxins in El Pañe Reservoir: A Threat for Water Quality in High-Andean Sources from PERU - Victor Hugo Rodriguez Uro; Joana Azevedo; Mário Jorge Araújo; Raquel Silva; Jürgen Bedoya; Betty Paredes; Cesar Ranilla; Vitor Vasconcelos; Alexandre Campos (Toxins)
Cyanobacteria are cosmopolitan organisms; nonetheless, climate change and eutrophication are increasing the occurrence of cyanobacteria blooms (cyanoblooms), thereby raising the risk of cyanotoxins in water sources used for drinking, agriculture, and livestock. This study aimed to determine the presence of cyanobacteria, including toxigenic cyanobacteria and the occurrence of cyanotoxins in the El Pañe reservoir located in the high-Andean region, Arequipa, Peru, to support water quality management. The study included morphological observation of cyanobacteria, molecular determination of cyanobacteria (16S rRNA analysis), and analysis of cyanotoxins encoding genes (mcyA for microcystins, cyrJ for cylindrospermopsins, sxtl for saxitoxins, and AnaC for anatoxins). In parallel, chemical analysis using Liquid Chromatography coupled with Mass Spectrometry (LC-MS/MS) was performed to detect the presence of cyanotoxins (microcystins, cylindrospermopsin, saxitoxin, and anatoxin, among others) and quantification of Microcystin-LR. Morphological data show the presence of Dolichospermum sp., which was confirmed by molecular analysis. Microcystis sp. was also detected through 16S rRNA analysis and the presence of mcyA gene related to microcystin production was found in both cyanobacteria. Furthermore, microcystin-LR and demethylated microcystin-LR were identified by chemical analysis. The highest concentrations of microcystin-LR were 40.60 and 25.18 µg/L, in May and November 2022, respectively. Microcystins were detected in cyanobacteria biomass. In contrast, toxins in water (dissolved) were not detected. Microcystin concentrations exceeded many times the values established in Peruvian regulation and the World Health Organization (WHO) in water intended for human consumption (1 µg/L). This first comprehensive report integrates morphological, molecular, and chemical data and confirms the presence of two toxigenic cyanobacteria and the presence of microcystins in El Pañe reservoir. This work points out the need to implement continuous monitoring of cyanobacteria and cyanotoxins in the reservoir and effective water management measures to protect the human population from exposure to these contaminants.